Drug interactions with new hepatitis C oral drugs. (March 2015) - Soriano, Vincent; Labarga, Pablo; Barreiro, Pablo; Fernandez-Montero, José V; de Mendoza, Carmen; Esposito, Isabella; Benítez-Gutiérrez, Laura; Peña, José M
<x xml:space="preserve">Abstract</x> Introduction: Chronic hepatitis C virus (HCV) infection has recently become a curable disease with antiviral therapy. The knowledge of drug interactions using direct-acting antivirals (DAA) may permit maximizing antiviral efficacy and avoiding drug-related toxicities. Ageing in the chronic hepatitis C population, along with added co-morbidities that require other medications, has increased the attention on drug interactions using DAA. Areas covered: This review provides an update of the most clinically significant pharmacokinetic and pharmacodynamic drug interactions occurring between currently available DAA and other medications. The review also revisits how drug interactions with DAA can be prevented and managed. Expert opinion: Interactions between DAA and other drugs are frequent in clinical practice. The most frequent drug interactions modify drug metabolism by inducing or inhibiting the cytochrome P450, leading to abnormal drug exposures. Through this mechanism HCV protease inhibitors, especially when co-formulated with ritonavir as pharmacoenhancer, and non-nucleoside HCV polymerase inhibitors interact with other medications. In contrast, NS5B nucleos(t)ide analog inhibitors (i.e., sofosbuvir) and some HCV NS5A inhibitors (i.e., ledipasvir), which do not or only marginally affect CYP450, are relatively free of significant pharmacokinetic interactions. However, exposure to HCV nucleos(t)ide analogs may be influenced by induction/inhibition of drug transporters (i.e., P-glycoprotein) as well as by pharmacodynamic interference with other nucleos(t)ide analogs used as antivirals or cancer drugs. Drug interactions for some NS5A inhibitors (i.e., daclatasvir) are generally moderate and can be managed with dose adjustments.